Post-Pandemic Indonesian Tourism Promotion in Instagram: Multimodal Discourse Analysis - Isti'anah, Arina; Rahmasari, Shafira; Lauwren, Stefanny (Journal of Modern Languages, 2021)
Tourism is one of the most significant sectors affected by the covid-19 pandemic. It has lost billions of dollars due to hotels, restaurants, and visit cancellation. The Indonesian Ministry of Tourism and Creative Economy uses social media to arouse people’s optimism to visit Indonesia in the post-pandemic era. One of the media used to promote tourism is through Instagram, which includes both visual and linguistic features in its uploads. By taking the data during October-November 2020 from Indonesia.travel Instagram account, this paper utilized Kress & Leeuwen’s multimodal discourse analysis model, particularly the interactive meanings of pictures through contact, distance, and point of view. This paper also analyzed the mood structures and transitivity patterns in the captions, including the phrase like “post-pandemic trip” to strengthen the analysis. It figured out that Instagram posts comprise Indonesian nature, cultural heritage, and traditional villages in declarative mood functioning as “offer”. This paper concluded that visual features are as pivotal as linguistic features to promote Indonesian tourism in the post-pandemic era.